2018
DOI: 10.1097/jcn.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Implant Strategy–Specific Changes in Symptoms in Response to Left Ventricular Assist Devices

Abstract: There are many differences in the magnitude and timing of change in symptom responses to LVAD between bridge and destination therapy patients. Detailed information on changes in specific symptoms may better inform shared decision-making regarding LVAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The two-year survival of LVAD patients, when compared with optimal medical management (OMM) patients in INTERMACS 4 group met all-composite end-point with improvements in (1) New York Heart Association (NYHA ) functional class (≥1 class), (2) EuroQoL (EQ)-5D visual analog scale (VAS) (>20 points), and (3) Patient Health Questionnaire - 9 (PHQ-9) score (≥5 points) (P<0.001) [ 19 ]. In a study by Lee et al, during the follow-up period of 6 months, LVAD patients in both patient groups (destination therapy and bridge to transplant) showed similar significant improvements in HRQOL, and significant improvement in shortness of breath, while moderate to significant improvements in wake disturbances [ 20 ]. A similar study, also conducted by Lee et al, showed significant improvement in shortness of breath (<0.001) and fatigue within 30 days after LVAD implantation, which was followed by subsequent improvement through 180 days [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…The two-year survival of LVAD patients, when compared with optimal medical management (OMM) patients in INTERMACS 4 group met all-composite end-point with improvements in (1) New York Heart Association (NYHA ) functional class (≥1 class), (2) EuroQoL (EQ)-5D visual analog scale (VAS) (>20 points), and (3) Patient Health Questionnaire - 9 (PHQ-9) score (≥5 points) (P<0.001) [ 19 ]. In a study by Lee et al, during the follow-up period of 6 months, LVAD patients in both patient groups (destination therapy and bridge to transplant) showed similar significant improvements in HRQOL, and significant improvement in shortness of breath, while moderate to significant improvements in wake disturbances [ 20 ]. A similar study, also conducted by Lee et al, showed significant improvement in shortness of breath (<0.001) and fatigue within 30 days after LVAD implantation, which was followed by subsequent improvement through 180 days [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…In some situations we already know which trajectory participants should fall; this may be the case when applying LGMM to experimental designs, or if there are known differences between patient groups (this is called "known class" analysis -see example comparing patients who received an LVAD as a bridge to transplantation vs as destination therapy). 19 But, it is more often the case that we do not yet know which trajectory participants belong to, and therefore have to begin the iterative process of identifying the number of trajectories, and allow participant membership in trajectories to be data-driven.…”
Section: Model Specificationmentioning
confidence: 99%
“…Common extensions of LGMM, including predicting trajectory membership, 7,11,24,25 known group analysis, 8,19 and linking trajectories to outcomes, 5 are presented in Table 3.…”
Section: Latent Mixture Modeling Extensionsmentioning
confidence: 99%
See 2 more Smart Citations